How arteriovenous grafts could help to optimize vascular access management. Issue 6 (1st June 2018) - Besarab, Anatole; Kumbar, Lalathaksha
Abstract: A one‐size‐fits‐all approach to vascular access for dialysis may be prejudicial. Arteriovenous fistulae (AVF) have high primary failure, failure to mature rate, and late‐stage complications making them unsuitable choice for many patients. Aging of population with chronic kidney disease (CKD) coupled with venous injury during CKD stages depletes suitable superficial veins for AVF creation. The National Institutes of Health consortium demonstrated the difficulty in attaining a functional AVF in hemodialysis patients. Recognition of flaws in AVF and the quest to reduce catheter use bring to the fore the benefits of arteriovenous grafts (AVG). Advances in catheter technologies, flow, care, and antibiotic locks have resulted in significant improvement in catheter‐related infections. However, widespread recognition of catheter‐related complications like central vein stenosis, metastatic infections, and exhaustion of venous access sites preclude their being a viable alternative to AVF, furthering the need to explore AVG as a substitute. Placement of "early cannulation" AVG is a catheter sparing option in patients who are likely to have inadequate fistula maturation. Advances in biohybrid technology and tissue‐engineered grafts are providing a robust opportunity to develop biocompatible graft materials with minimal tissue reactivity and thrombogenicity. Xenografts (bovine carotid artery grafts) are proving to be comparable and, in many cases, better than conventional polytetrafluoroethylene material. Older age, dialysis dependence, and smaller vein size are related to the appropriateness of AVG creation. An individualized approach in selecting optimal upper extremity vascular access option using patient‐specific factors while incorporating the benefits of an AVG would greatly aid in achieving low catheter usage in the dialysis population.